2018
DOI: 10.12691/ajmcr-5-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Bilateral Breast Cancer (SBBC): Report of a Case with Review of Literature

Abstract: The incidence of synchronous bilateral invasive breast cancer (SBBC) is reported to range from 0.8%-3.0%. Lower disease-free survival and high rates of distant metastasis is a recognized feature of bilateral synchronous tumors, which therefore have a worse overall survival compared to unilateral tumors. Early detection of the contralateral tumor is of utmost importance emphasizing the significance of breast self-examination. Here we report a case of SBBC with invasive ductal carcinoma on both sides in a 50-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recently, the NCCN has endorsed the 21-gene RT-PCR assay or Oncotype Dx testing for most endocrine receptor positive breast cancers to determine the likelihood of adjuvant chemotherapy followed by adjuvant endocrine therapy compared to adjuvant endocrine therapy alone [1]. However, the NCCN guideline does not address how to apply the assay to estimate of recurrence risk from one or the other or both cancers for that small percentage of patients with synchronous breast cancers (1–3%), although studies have shown that the risk of recurrence from one, the other or both, is higher than the risk from either of individual cancer [2, 3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the NCCN has endorsed the 21-gene RT-PCR assay or Oncotype Dx testing for most endocrine receptor positive breast cancers to determine the likelihood of adjuvant chemotherapy followed by adjuvant endocrine therapy compared to adjuvant endocrine therapy alone [1]. However, the NCCN guideline does not address how to apply the assay to estimate of recurrence risk from one or the other or both cancers for that small percentage of patients with synchronous breast cancers (1–3%), although studies have shown that the risk of recurrence from one, the other or both, is higher than the risk from either of individual cancer [2, 3, 4].…”
Section: Discussionmentioning
confidence: 99%